The Effectiveness of Student Worksheet with Problem Based Learning and Ethnoscience to Improve Critical Thinking Skills on Chemical Bonding Material: - - Rahmawati, Audy Via; Muchlis, Muchlis (UNIB Press, 2025)
Learning chemistry through the merdeka curriculum prioritize on enhancing 21st century skills include students' critical thinking skills. Due to a number of critical thinking skill constraints, students find out the difficulties to comprehend theory-based in chemistry materials, such as chemical bonding materials. By problem-based learning that integrates ethnoscience content can make learning more meaningful is a way to train and enhance critical thinking skills. This research conducted in terms to quantify the effectiveness of Problem Based Learning and ethnoscience-based student worksheet on chemical bonding material to enhance the critical thinking skills of XI grade senior high school students. The research method used are descriptive quantitative and qualitative of One Group Pretest-Posttest Design. With 36 students of class XI-8 in SMAN 16 Surabaya as the subject, the worksheet stated effective according to the increasingly of N-gain value with an average of 0.7206 that is in the high category. As much as 26 students include into the high category, 8 fall into the medium category, and 2 fall into the low category. Therefore, the finding suggest that student worksheet with Problem Based Learning and ethnoscience-based student worksheet on chemical bonding materials can significantly improve students’ critical thinking abilities.